Control of Meloidogyne javanica by Formulations of Inula viscosa Leaf Extracts - Oka, Yuji (The Society of Nematologists, 2006)
Inula viscosa is a perennial plant that is widely distributed in Mediterranean countries. Formulations of I. viscosa extracts were tested for their effectiveness in control of Meloidogyne javanica in laboratory, growth chamber, microplot, and field experiments. Oily pastes were obtained by extraction of dry leaves with a mixture of acetone and n-hexane or n-hexane alone, followed by evaporation of the solvents. Emulsifiable concentrate formulations of the pastes killed M. javanica juveniles in sand at a concentration of 0.01% (paste, w/w) or greater and reduced the galling index of cucumber seedlings as well as the galling index and numbers of nematode eggs on tomato plants in growth chamber experiments. In microplot experiments, the hexane-extract formulation at 26 g paste/m(2) reduced nematode infection on tomato plants in one of two experiments. In a field experiment, a reduction of 40% in root galling index by one of two formulations was observed on lettuce plants. The plant extracts have potential as a natural nematicide, although the formulations need improvement.